Avaliação de impacto e análise de vulnerabilidade ambiental para extração de rochas ornamentais do Espírito Santo - Amarante, Leonardo Monjardim (2019)
Many projects implemented in the ornamental stone mining sector are quite different from those that had been described in the presented environmental studies, making it difficult or even impossible to compare the predicted and verified impacts after the project has been completed. In addition, when mining activities cause a disturbance, the response of the environment may be quite different depending on the natural and human characteristics of the site. This research considers the concept of natural vulnerability evaluating the quality of environmental studies and their agreement with the resolutions and best practices of the sector, with the purpose of verifying the compatibility with the environmental, social and economic characteristics of each region, besides suggesting guidelines for the terms of reference that guide the preparation of these studies. For the development of the present work tools have been applied that consider eight Legal Variables (VL) divided into 34 (thirty four) items and used to analyze the agreement with the legislation. We also considered 5 (five) Technical Variables (VT) divided into 15 (fifteen) items of interest for the analysis of the technical aspects addressed. The companies with the highest volume of ore production in the state of Espírito Santo identified with valid operating licenses, and possible to analyze environmental studies, were considered. Of the 267 companies that extract ornamental rocks, 65 environmental studies were evaluated, 26% presented "low" agreement with legal variables, 72% were classified with "average" agreement and only one environmental study was classified as "high" agreement with related to legislation. Regarding the technical aspects evaluated, 64.5% of the studies were classified with "low" agreement and 35.5% with "average", no study was classified with "high" agreement, which suggests the lack of qualified professionals in the elaboration of reports, plans and projects in this sector. In terms of vulnerability, 33% of the deposits are in areas of "very low" vulnerability and 26% in areas of "low" vulnerability. Thus, 59% of the areas of ornamental stone mining companies object of the present study were installed in places with favorable vulnerability for operation and extraction. On the other hand, 22% of the deposits are located in areas of "high" or "very high" vulnerability, indicating the need for environmental studies compatible with these indices (technical and legal quality). Only 19% of the quarries were located in areas of "average" vulnerability. In addition, it is argued that the determination of the type of environmental study should not only be based on the size of the enterprise and its monthly production in cubic meters, but also consider the natural vulnerability of the areas of direct and indirect influence. The results indicated that many mining companies did not contemplate fundamental items of significant importance in the evaluation of environmental impacts, such as: the definition of an indirect area of influence, a description of the impacts and proposition of measures on the anthropic environment, besides the definition of programs of monitoring. Therefore, it is essential that the studies are reviewed by the competent environmental agency through terms of reference (TR) according to the local vulnerability.